Diabetes in Elderly and its Management from Ayurvedic and Modern Approach – A Review - Kaushik, Jyoti; Kumar, Ajay; Singhal, Tina; Vats, Bharti (International Research Journal of Ayurveda & Yoga, 2023)
Old age presents with serious challenges and changes for their own and their family. As the age grows, a person’s body may no longer feel familiar, physical activity greatly reduced, memory starts going fade and person become full of many diseases. Diabetes is also one of them. About 40% population in India of diabetes is greater than age 65 years. Old patients having diabetes have high risk of occurrence of secondary complications such as fragility, cognitive impairment, traumatic fall, fractures, and other neuropathies. Hence, need of care and management is at most important for old age diabetes. Diabetes Type-2 may be somewhat similar to Madhumeha in Ayurveda. Vagabhatta has classified Madhumeha into two categories: These are Dhatukshaya-janaya Madhumeha and Avarana-janya Madhumeha. The factors which provoke Vata directly cause Apatarparjanya Madhumeha and the factors which provoke Kapha and Pitta cause Santarpanajanya Madhumeha. In the former type, patients are usually asthenic that can be correlated with diabetes mellitus Type I and in latter type patients are obese and can be equated with Type II diabetes mellitus. Hence, Kapha and Pitta Shamak Aushadhi and dietary restrictions are best for the management of elderly diabetes. The management of Type 2 Diabetes mellitus in older adults is complicated than younger individuals because of the frequent occurrence of multimorbidity, necessitating highly individualized approaches. Here, a complete review by Modern and Ayurvedic approach is taken to the assessment, nursing care, and medical treatment of diabetes in the elderly.